2016
DOI: 10.1007/s00348-016-2290-x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments to investigate lift production mechanisms on pitching flat plates

Abstract: exo-planetary exploration (Young et al. 2000). MAVs can use flapping wing designs to take advantage of unsteady effects at low Reynolds numbers (Petricca et al. 2011). Flapping wing-style MAV designs could be improved with a better understanding of the governing physics of flapping wing motions. For example, more efficient flapping movements could provide longer battery life and hence increase flight duration. Of particular interest in the generation of an efficient motion is the fluid mechanical process by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It has also been shown that in contrast to the assumptions made in these models, bound circulation is small in rapidly accelerating wings at large incidence, where flow separates at the leading edge to form a vortex [4]. Therefore, numerous studies have investigated the effect of the leading edge vortex (LEV) as well as on developing reduced low order models to predict the force response [5][6][7]. Being able to quickly model the forces, will allow for improved safety as well as provide the tools to design broader operating windows.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that in contrast to the assumptions made in these models, bound circulation is small in rapidly accelerating wings at large incidence, where flow separates at the leading edge to form a vortex [4]. Therefore, numerous studies have investigated the effect of the leading edge vortex (LEV) as well as on developing reduced low order models to predict the force response [5][6][7]. Being able to quickly model the forces, will allow for improved safety as well as provide the tools to design broader operating windows.…”
Section: Introductionmentioning
confidence: 99%
“…Beckwith & Babinsky (2009) demonstrate experimentally that the impermeable Wagner function predicts well the lift history at long times for small angles of attack, where measured early-time responses overshoot the theoretical predictions due to delayed stall effects not present in the Wagner model. Larger impulsive changes to the angle of attack lead to persistent nonlinear flow structures that must be integrated into the aerodynamic lift model to improve its predictive capacity (Pitt Ford & Babinsky 2014; Li & Wu 2015; Stevens & Babinsky 2017). However, unsteady porous aerofoils may introduce important nonlinear flow features in real flows even at small angles, and an experimental campaign beyond the scope of the present work is needed to examine the relevant fluid mechanics of porous aerofoils and the predictive capability of the present model.…”
Section: Porous Extensions Of Standard Unsteady Aerodynamic Functionsmentioning
confidence: 99%
“…Thus, it makes sense that some have analyzed a pitching motion in regard to unsteady flows and gust encounters. One such work by Stevens and Babinsky examines both the flow structure itself as well as the forces and moments generated by such a motion [72].…”
Section: Oscillating Vanes and Shutter Gust Generatorsmentioning
confidence: 99%